Learning Activities Management based on Buddhism learning approach to Enhance Ethical Behaviors of student teachers in the College of Dramatic Arts - Thintha , Piyabut (Journal for Developing the Social and Community, 2022)
The purposes of this research were: 1) to develop learning activities management based on Buddhism Learning Approach to enhance Ethical Behaviors of Student Teachers in the College of Dramatic Arts 2) to study about ethical behavior in learning activities management based on Buddhism Learning Approach of student teachers in the College of Dramatic Arts 3) to compare the Ethical Behaviors of student teachers in the College of Dramatic Arts after finish the activities based on Buddhism Learning Approach with the criteria for 70 percent and 4) to study about behavior development among student teachers in the College of Dramatic Arts. The populations in this research were 28 people of first year students in the College of Dramatic Arts which registered in this subject – the Ethical to develop life quality in the modern world. This subject was held in second semester of 2020. The tools for this research including six lesson plans and the Ethical behavior assessment form. The research used percentage, mean and standard deviation to analyze the information. The result from this research found that 1) the lesson plans that based on Buddhism Learning Approach had high suitability ( = 4.47, S.D. = 0.58). There were four steps to create activities: 1) built the faith 2) explored and developed the wisdom 3) analyzed the knowledge and 4) applied. In addition, the students had the highest Ethical behavior level (µ = 4.64, σ= 0.52). Moreover, the students’ Ethical behavior was passed the criteria with average for 91 percent which higher than the expected criteria. Lastly, the Ethical behavior of students also develop more.